Intertextuality and its Analysis in Interpretation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article attempts to present and illustrate the term intertextuality as a concept and as a method that can offer a framework for the analysis and interpretation of short stories or life stories. Intertextuality, as one of the central concepts in the study of culture, is particularly suited to qualitative research, which focuses on the subjectivity of the narrator, the story and the listener/researcher, as well as the relative and indefinite dimension of knowledge. However, the use of intertextuality as an interpretative method in various types of texts requires the knowledge and ability of the researcher in the areas considered in this article.